Privatization, competition and corruption: How characteristics of bribe takers and payers after bribe payments to utilities - George R. G. Clarke; Lixin Colin Xu (Fondazione Eni Enrico Mattei (FEEM), 2002)
Many recent studies have looked at the macroeconomic, cultural and institutional determinants of corruption at the cross-national level. This study complements these existing cross-country studies by focusing on firm-level evidence of microeconomic factors affecting bribes paid in a single sector of the economy. Using enterprise-level data on bribes paid to utilities in 21 transition economies in Eastern Europe and Central Asia, we examine how characteristics of the utilities taking bribes and the firms paying bribes affect the equilibrium level of corruption in the sector. Bribe takers (utility employees) are more likely to take bribes in countries with greater constraints on utility capacity, lower levels of competition in the utility sector, and where utilities are state-owned. Bribe payers (enterprises) are more likely to pay bribes when they are more profitable, have greater overdue payment to utilities, and are de novo private firms. A thorny issue in the empirical literature on corruption is how to distinguish between the "endogenous harassment" and "speed money" theories of corruption. The former receives stronger support from some of the results than the latter.
Keywords: K4; L1; L9; 330; Corruption; bribes; ownership; competition and privatization; Korruption; Privatisierung; Versorgungswirtschaft; Übergangswirtschaft; Osteuropa; GUS-Staaten